Orchids of cloud forest in Genting Highlands, Pahang, Malaysia - Ng, Yong Jin; Go, Rusea; Rosimah Nulit; Khor, Hong Eng; Tan, Mui Ching; Farah Alia Nordin; Ahmad Ainuddin Nuruddin, Nam Sook; Lee (Universiti Kebangsaan Malaysia, 2012)
An inventory of orchid species diversity was carried out in cloud forest of Genting Highlands, which is one of the most developed highland areas in Peninsular Malaysia. Since 1967, construction of roads and hotel complexes has had a serious impact on its physical environment and vegetation. Habitat destructions together with climate change might have caused some orchid species to be extirpated locally or extinct. The cloud forest of Genting Highlands consists of four major peaks, Gunung Ulu Kali, Gunung Chin Chin, Gunung Lari Tembakau and Gunung Mengkuang. However, not much study on orchid diversity was conducted in these areas, therefore, this study is timely and essential to evaluate the current orchid diversity after a gap of three decades. Combined findings from the current study, previous published works and specimens deposited in local herbaria, including those at the Universiti Malaya, Universiti Kebangsaan Malaysia, Forest Researh Institute of Malaysia and Biology Department, Faculty of Science, Universiti Putra Malaysia and Singapore Botanic Gardens, an updated list of orchid species found in the cloud forests of Genting Highlands is presented. A total of 134 orchid taxa were recorded, comprised of 51 genera, 132 species, 1 subspecies and 2 varieties, of which 46 are new records to Genting Highlands. Hymenorchis javanica, a species previously reported as endemic to West Jawa was recently discovered in Gunung Ulu Kali. Thirty-three species discovered during this study are currently classified as endemic to Peninsular Malaysia, of which 20 are endemic to Pahang, Perak and Selangor and a very narrowly endemic species; Corybas villosus to Gunung Ulu Kali. Through our observations, most of the orchid species in Gunung Ulu Kali are very susceptible to disappearance due to loss of habitat and local climate change. An assessment of conservation status according to IUCN criterion revealed that 47 orchid taxa from Gunung Ulu Kali were threatened with extinction. Conservation actions were suggested to conserve the orchid diversity in the cloud forest areas of Genting Highlands.